Pelvic floor dysfunction: prevalence and associated factors - Rocío Adriana Peinado-Molina; Antonio Hernández-Martínez; Sergio Martínez-Vázquez; Julián Rodríguez-Almagro; Juan Miguel Martínez-Galiano (BMC, 2023)
Abstract Background Pelvic floor dysfunction in women encompasses a wide range of clinical disorders: urinary incontinence, pelvic organ prolapse, fecal incontinence, and pelvic-perineal region pain syndrome. A literature review did not identify any articles addressing the prevalence of all pelvic floor dysfunctions. Objective Determine the prevalence of the group of pelvic floor disorders and the factors associated with the development of these disorders in women. Material and methods This observational study was conducted with women during 2021 and 2022 in Spain. Sociodemographic and employment data, previous medical history and health status, lifestyle and habits, obstetric history, and health problems were collected through a self-developed questionnaire. The Pelvic Floor Distress Inventory (PFDI-20) was used to assess the presence and impact of pelvic floor disorders. Pearson's Chi-Square, Odds Ratio (OR) and adjusted Odds Ratio (aOR) with their respective 95% confidence intervals (CI) were calculated. Results One thousand four hundred forty-six women participated. Urinary incontinence occurred in 55.8% (807) of the women, fecal incontinence in 10.4% (150), symptomatic uterine prolapse in 14.0% (203), and 18.7% (271) reported pain in the pelvic area. The following were identified as factors that increase the probability of urinary incontinence: menopausal status. For fecal incontinence: having had instrumental births. Factors for pelvic organ prolapse: number of vaginal births, one, two or more. Factors for pelvic pain: the existence of fetal macrosomia. Conclusions The prevalence of pelvic floor dysfunction in women is high. Various sociodemographic factors such as age, having a gastrointestinal disease, having had vaginal births, and instrumental vaginal births are associated with a greater probability of having pelvic floor dysfunction. Health personnel must take these factors into account to prevent the appearance of these dysfunctions.